Curriculum and Arabic Language Learning Management at MQW JIC Islamic Boarding School Surakarta - Ahmad Nur Hafid; Saiful Islam; Mafidatul Ilmi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Curriculum and Arabic language learning management play a crucial role in improving the quality of education in Islamic boarding schools. Curriculum management encompasses the interrelated stages of planning, implementation, and evaluation to ensure that educational objectives are effectively achieved. This study aims to analyze the curriculum and Arabic language learning management at Madrasatul Qur’an Al-Mutawassithoh (MQW), JIC Islamic Boarding School Surakarta, focusing on the stages of planning, implementation, and evaluation. This research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The findings indicate that teachers have made efforts to prepare lesson plans, select various teaching methods and strategies, and utilize Arabic textbooks, although these activities are not yet formally documented. Evaluation is conducted through daily assignments, speaking practice, oral and written examinations, as well as Mid-Semester (PTS) and Final-Semester (PAS) assessments. In addition, remedial classes are provided for students with lower proficiency, offered to parents as a supplementary learning program. The study concludes that curriculum management for Arabic language learning at MQW JIC Surakarta has been implemented through systematic stages of planning, implementation, and evaluation; however, further improvement is needed in formal planning and documentation of instructional tools to enhance effectiveness.